Optimalisasi Dui Menre’ dalam Pemanfaatan Ekonomi Keluarga Ditinjau dari Perspektif Maqasid Al-Syari’ah: Studi pada Masyarakat Bugis di Kabupaten Bone - Sakirah; Abdulahanaa; Hukmiah Husain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the optimisation of Dui Menre’ in the economic utilisation of families, analysed from the perspective of Maqasid Al-Syari’ah, focusing on the Bugis community in Bone Regency. The research aims to ascertain the impact of dui Menre’ on the economic welfare of families post-marriage, how the Bugis community optimises dui Menre’, and what strategies can be implemented in the management of dui Menre’ for family economic utilisation. Additionally, it examines how this can be integrated with the principles of Maqasid Al-Syari’ah. The methodology employed in this research is qualitative descriptive, with field research as its primary approach. Data collection techniques included interviews, questionnaires, observations, and documentation. The findings indicate that dui Menre’ within the Bugis community in Bone Regency has yet to be utilised optimally. The funds allocated for dui Menre’ are primarily expended on wedding celebrations. The economic impact on families results in newly married couples lacking independence, progression, and financial prosperity post-marriage. These consequences contradict the principles of Maqasid Al-Syari’ah, which can threaten the preservation of hifz al-di>n (protection of religion), hifz al-nafs (protection of life), hifz al-‘aql (protection of intellect), hifz al-nasl (protection of lineage), and hifz al-mal (protection of wealth). Strategies to optimise dui Menre’ include avoiding the excessive expenditure on lavish celebrations by simplifying the concept of the wedding. Furthermore, setting aside a portion of dui Menre’ for savings and investments can support the household needs of newlyweds post-marriage.